COVID‐19 and thalassaemia: A position statement of the Thalassaemia International Federation. (13th July 2020) - Farmakis, Dimitrios; Giakoumis, Anastasios; Cannon, Lily; Angastiniotis, Michael; Eleftheriou, Androulla
Abstract: Objectives: Many patients with haemoglobinopathies, including thalassaemia and sickle cell disease, are at increased risk of developing severe complications from the coronavirus disease 2019 (COVID‐19). Although epidemiologic evidence concerning the novel coronavirus (SARS‐CoV‐2) infection in these patients is currently lacking, the COVID‐19 pandemic represents a significant challenge for haemoglobinopathy patients, their families and their attending physicians. Methods: The present statement summarizes the key challenges concerning the management of haemoglobinopathies, with particular focus on patients with either transfusion‐dependent or non‐transfusion‐dependent thalassaemia, identifies the gaps in knowledge and suggests measures and strategies to deal with the pandemic, based on available evidence and expert opinions. Key areas covered include patients' risk level, adaptation of haemoglobinopathy care, safety of blood transfusions, blood supply challenges, and lifestyle and nutritional considerations. Conclusions: The proposed measures and strategies may be useful as a blueprint for other disorders which require regular hospital visits, as well as for the timely adaptation of patient care during similar future pandemics.